CHILDFREE IN THE PERSPECTIVE OF ISLAMIC LAW AND COMMUNITY VIEWS IN ASAHAN DISTRICT - Putri Setia Ningsih; Faisal Faisal; Malahayati Malahayati (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
Childfree is a choice made by a person or married couple who do not want to have children after marriage, whether biological children, stepchildren, or adopted children. The assumption is that the inability of a person or partner to be responsible for having children, fear, and financial conditions are the main factors in choosing childfree. This study is related to childfree ness in the perspective of Islamic law and the views of the people of Asahan Regency, and its impacts. The method in this study is qualitative research, with an empirical juridical approach. Descriptive nature with data collection techniques using field study techniques and literature review. The results of the study show that from an Islamic perspective, childfree is carried out by permanently disabling the reproductive system, so the law is unlawful. However, if it is done in a temporary period then the law is makruh because basically having children is a recommendation, not an obligation. This is also in line with Article 1 of Law Number 1 of 1974 concerning Marriage. In the opinion of some people in Asahan Regency, the choice of childfree is a private right of a person which cannot be questioned because basically in the 1945 Constitution Article 28E paragraph (2) stipulates that everyone has the right to freedom of expression of thoughts and attitudes according to their conscience, however, some others argue that the childfree choice in society is considered a selfish choice and violates nature. In addition, the impact of choosing childfree, especially for women, has a high risk in terms of health.